PECULIARITIES OF THE LEGAL REGULATION OF THE LABOR OF SOME CATEGORIES OF EMPLOYEES - Ayupova, Z.K.; Kussainov, D.U.; Nagan, Winston; Seitakhmetova, N.L. (Scientific Journal of Pedagogy and Economics, 2020)
Research on the specifics of the legal regulation of certain categories of employees is conducted by leading foreign research centers and international organizations. In particular, the work of women, children, disabled people, homeworkers, seasonal workers and migrants is one of the most active research topics within the UN, ILO, OSCE, and CIS. For example, the topics are “Labor Market Trends and Outlook”, “Labor, Income and Equity”, “Changing World of Work”, “Macroeconomic Policies and Jobs”, “Globalization and Labor Market”, “Policy evaluation”, “Youth and Gender Issues” (Special issues of youth and gender are also covered) are recognized as one of the main topics studied by the ILO Research Department in The direction of labor market trends and prospects. The following results were obtained in scientific studies conducted in the field of determining the features of legal regulation of labor of certain categories of workers in foreign countries: proposals were developed and implemented to ensure gender equality in labor relations (University of Sterling, Scotland), eliminate discrimination by introducing rules of differentiation (Rand Afrikaans University, South Africa), and provide additional opportunities in the field of labor for women and persons employed in family responsibilities (University of Essex, UK), increasing the role of contracts in regulating the work of home workers (Middlesex University, UK), providing equal rights in the use of migrant labor (University of Oxford, UK).